The elderly at the General Hospital and liaison psychiatry. - Cardoso, G; Ismail, F; Barbosa, A (Acta Médica Portuguesa, 1994)
It is known that in general hospitals there is an increasingly high percentage of elderly patients that frequently develop psychiatric morbidity during hospital stay. This has lead the authors to perform a comparative study involving patients referred to Consultation/Liaison Psychiatry, in order to establish guidelines for a future approach. The first 1.000 referrals to the Consultation/Liaison Psychiatry Unit of the Santa Maria Hospital were analysed by comparing patients aged 65 or above to other observed patients. The results indicate a clearly lower percentage of elderly patients referred and a longer average length of stay at the moment of referral. Medical diagnoses show a preponderance of cardiologic, malignant and respiratory diseases, whereas intoxication, the prime diagnosis in the younger group, is much less represented above the age of 65. Identically, referrals due to suicide attempt were significantly less frequent in this group. Psychiatric diagnoses show a greater prevalence of organic mental disorders, followed by mood disorders, while in the younger the latter prevail. The post-discharge plan shows a higher percentage of elderly patients referred to general practitioners and medical specialties and a lower one for psychiatric care, as opposed to the younger group. The conclusions point towards the need for programs directed to early detection and treatment of psychopathological disorders (organic and depressive mental disorders) of elderly people admitted to a general hospital. This will be achieved through a close collaboration between C/L psychiatrists and medical staff, families and community facilities.